A escala Servqual e o serviço de suporte aos usuários de um sistema de informação em uma instituição de ensino - Garcia, Augusto César Felisbino (2019)
The use of technological resources as a tool to manage information and optimize processes is increasingly present in organizational environments. Information systems are one of the technological resources used as tools for generating competitive advantage. However, these resources must be supported to effectively represent a competitive advantage for the organization, as well as to evaluate this support service. This research aimed to evaluate the quality perceived by users of the support service provided to the information system used for the academic management of an educational institution. For the evaluation, the Servqual model was used, with adaptations made considering the application context. The research has a quantitative approach and is characterized as a case study. Data collection was performed using electronic questionnaires and the sample collected by convenience was 194 respondents. For data analysis, normality tests, mean difference tests and regression analysis were used. We also calculated the difference between respondents' expectations and perceptions, identifying the gaps found in the quality of service. It was found that the Responsiveness dimension was the dimension that presented the biggest gap in quality of service, while the Reliability dimension had the smallest gap. Regression analysis allowed identifying that variables such as Sex and Age exert significant influence on certain items of the model. In general, it was noticed that the respondents consider that there is a gap in the quality of service in all items and dimensions addressed in the study.